Análise da eficiência energética de um sistema automatizado de controle de iluminação e condicionadores de ar implantado no Instituto Federal de Educação, Ciência e Tecnologia do Maranhão – IFMA – Campus Monte Castelo - COSTA, George Igor Cabral da (2018)
This work analyzed the electric energy consumption of the Automation Pilot Project for the control of the activation and shutdown of the lighting and air conditioners, installed in the rooms of the Technical Course in Occupational Safety of the IFMA Campus Monte Castelo; as well as, to measure the reduction of the waste of electric energy in the hours in which they are not taking classes, by comparing the energy consumption with and without the automated control system in operation. From this comparison, the energy efficiency of the control system was verified, as well as the quality of the electric power offered to the air conditioner and if the quality of the energy influences the increase of the consumption of the circuit. It was verified through the measurements that the quality of the energy offered to the room air conditioner's power circuit is within the standards required by the standard, not influencing the increase of the energy consumption. It was verified by the measurements that the energy consumption is less with the use of the automated system of control than with the manual system of activation and shutdown of illumination and air conditioner. In addition, it was concluded that, with the percentage of reduction of energy wastage obtained with the automated system of control of illumination and air conditioners in IFMA classrooms, it justifies the expenses with its implantation, besides showing that the automation of the control processes is a viable alternative for the reduction of the consumption of electric energy, and, consequently, contributing in the reduction of the environmental impacts provoked by the processes of generation of electric energy.